Cost-Effectiveness Analysis of Pembrolizumab Plus Chemotherapy vs. Chemotherapy Alone as First-Line Treatment in Patients With Esophageal Squamous Cell Carcinoma and PD-L1 CPS of 10 or More - Zheng, Zhiwei; Lin, Jingrong; Zhu, Huide; Cai, Hongfu (Frontiers in Public Health, 2022)
Background: This study was aimed to analyze the economics of pembrolizumab plus chemotherapy as first-line treatment in patients with esophageal squamous cell carcinoma(ESCC) and PD-L1 CPS of 10 or more in China Methods: Basis on the advanced ESCC of the KEYNOTE-590 clinical trial data, a Markov model was performed to simulate the clinical course and evaluate the patient’s total lifetime, total costs, quality-adjusted life-years (QALYs), incremental cost-effectiveness ratio (ICER) for pembrolizumab plus chemotherapy (cisplatin and 5-fluorouracil) versus chemotherapy alone in first-line treatment of ESCC and PD-L1 CPS of 10 or more. Utility values and direct costs related to the treatments were gathered from the published literature data. One-way and probability sensitivity analyses were conducted to check the stability in the model. Results: The baseline analysis indicated that the incremental effectiveness and cost of pembrolizumab plus chemotherapy versus chemotherapy alone added 1.23 QALYs and resulted in an incremental cost of $51320.22,which had an ICER of $41805.12/QALY, higher than the willingness-to-pay (WTP) threshold of China ($31,498.70/QALY). Sensitivity analysis demonstrated that the ICERs were most sensitive to the cycle of pembrolizumab used and the cost of pembrolizumab. Conclusion: The result of our present analysis suggested that addition of pembrolizumab plus chemotherapy as first-line treatment might not be cost-effective for patients with ESCC and PD-L1 CPS of 10 or more in China.